Study of the Optimal Parameters for the Formation of Selenium Complex with the (NEDA) N- (1-naphthyl-ethylenediamine dihydrochloride) C_12 H_14 N_(2. 2) 〖HCl〗_ Reagent and its use for the Control of Selenium Microcapsules - الشحنة, محمد; زم, وسام; حسن , عزيز علي (Latakia University Journal -Basic Sciences Series, 2020)
Selenium is an essential nutritional mineral, and selenium deficiency diseases are known in medical literature. Studies have shown that selenium intake in high doses is toxic in humans. Selenium is widely distributed in nature and due to the importance of selenium and its compounds in industrial applications; several analytical techniques have been reported to estimate selenium. In this study the optimal conditions for the formation of selenium complex with NEDA reagent will be studied and used for the control of selenium microcapsules, a method that is characterized by being rapid, sensitive and selective. The optical spectrophotometric method was used in the visible field at 540 nm wavelength to determine the complex between the selenium ion and the NEDA reagent under optimal conditions for complex formation namely temperature 50℃, time min t = 240, added reagent volume V=4ml, and reagent concentration 1%. This method showed good accuracy and correctness, as the method's validity was achieved through the relative percentage yield (R = 99.68%), while the accuracy of the method was achieved through the low value of the standard deviation (SD≤) (1.172) and thus the percentage relative standard deviation (RSD≤) (1.725). Selenium microcapsules were prepared, with an entrapment efficiency of 36% at a concentration of 3% for alginate and 1% while the entrapment efficiency rose to 51.2% at a concentration of 2% for calcium chloride.